The Validity of Ultrasound KUB; in the Diagnosis of Ureteric Calculus - Faiza Akram, Waleed Khan, Muhammad Fayyaz, Syed Komal Siraj, Faizan Banaras (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Diagnostic techniques have utilized to diagnose ureteric calculus in patients presenting with ureteric calculus. The availability, cost and expertise of these techniques varies greatly from region to region. Among them ultrasound is the widely available, can be rapidly performed and also can be repeated without any exposure to radiation. We conduct this study which helps to establish the level of sensitivity, the specificity level, the value of Positive Prediction and the value of the negative prediction KUB ultrasound in the diagnosis of ureteric calculus. Methods: They collect this data from 193 patients from suspected ureteric calculus. All these 193 patients underwent for Ultrasound KUB followed by non-contrast CT KUB. These results of ultrasound are compared with CT KUB, which helps to report and to determine the accuracy level of ultrasound. Results: The USG enables and helps diagnose 105 number of cases in 193 patients with the accuracy of 62.60%. Number of cases diagnosed as having ureteric calculus on CT KUB, were 171 out of total 193 patients with 22 cases being missed. Conclusions: This ultrasound is a key to the preliminary test for the diagnosis of ureteric calculus. These results show some significant relationship for the last and final CT KUB report. The Professional level of experts used to perform this task.